TRANSKULTURASI DALAM PENERJEMAHAN PRONOMINA PADA TERJEMAHAN ALQURAN BAHASA SUNDA - Syihabuddin, Syihabuddin (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2018)
The pronouns of Arabic are different from the pronouns of Sundanese. Arabic pronouns have egalitarian and neutral meanings, while Sundanese pronouns reveal the dimensions of socio-cultural and politeness. If the pronouns of the two languages are expressed in translation, how would linguistic devices respond to the transculturation between the two languages?  To answer this question, the data were collected from the translation of the Arabic pronouns in the Qur'an Surah Ali 'Imran and used semantic analysis method to compare the lexical, contextual, and pragmatic meanings of the two languages.  From 14 Arabic pronouns, only 9 pronouns were translated variably. The translation is capable of equally conveying the concept of quantity ('adad) in the recipient language through the affixation process, but has not been able to address the gender aspect. The translation also considered the interpersonal meaning and the relationship of the interlocutors. This is a form of transculturation from being neutral, egalitarian, and exclusive to become partial, inclusive, polite, and communicative.